En retrospectiva: Estrella distante de Roberto Bolaño - Guadalupe Gerardi (Caravelle)
This article explores the ways in which crime fiction and central tenets of the avant-garde are combined in Roberto Bolaño’s Estrella distante (1996) as means to re-evaluate the legacy of Augusto Pinochet’s dictatorship in Chile. This reading proposes that the novel’s re-working of the genre and the use of aesthetic motives related to ideas of newness and participation act as a platform to reformulate notions of responsibility and justice and, fundamentally, patterns of continuity between the dictatorship and the post-dictatorship period.